Sterilisasi Peralatan dan Media Kultur Jaringan - Sri Wulandari; Yonita Sholihatun Nisa; Taryono Taryono; Siwi Indarti; Rahmi Sri Sayekti (Agrotechnology Innovation (Agrinova), 2021)
Plant tissue culture is a technology used to propagate plants under controlled and aseptic environmental conditions. One of the obstacles in tissue culture activities is the presence of bacterial and fungal contamination. Equipment and growing media that are used for tissue culture can be the source of contamination. The method that can be used to reduce contamination is using sterilization. Sterilization is used to kill or eliminate microorganisms so that the equipment and media are free from contaminants. Equipment sterilization can be done through several methods such as wet sterilization and dry sterilization. Wet sterilization is carried out using an autoclave, while dry sterilization can be carried out using an oven, fire, and glass bead sterilizer. Media sterilization is generally carried out using an autoclave or membrane filter.